2021
DOI: 10.1108/idd-04-2020-0036
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing scholarly publication productivity: a systematic review

Abstract: Purpose The importance of scientific publications has enhanced the research activities at all aggregate levels. The purpose of this paper is to conduct an in-depth review of studies examined the factors that influence the publication productivity among researchers, institutions and countries. Design/methodology/approach This paper uses a systematic literature review approach that is based on relevant literature retrieved from two authentic and well-known databases named Web of Science and SCOPUS. Kitchenham … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 52 publications
3
30
1
Order By: Relevance
“…Unlike our ndings, previous studies showed that the highest quali cation and current job classi cation level predicted research engagement (25,29). A review conducted by Wahid et al (42) revealed that quali cation was the primary determinant factor affecting research publication productivity. The disagreement between these ndings could be attributed to variations in the study participants.…”
Section: Factors Affecting Article Publication and Presentation Confe...contrasting
confidence: 90%
“…Unlike our ndings, previous studies showed that the highest quali cation and current job classi cation level predicted research engagement (25,29). A review conducted by Wahid et al (42) revealed that quali cation was the primary determinant factor affecting research publication productivity. The disagreement between these ndings could be attributed to variations in the study participants.…”
Section: Factors Affecting Article Publication and Presentation Confe...contrasting
confidence: 90%
“…While prior research has studied correlates of research productivity across a variety of fields such as higher education (Dundar and Lewis, 1998), information science (Abramo et al ., 2017), management (Valle and Schultz, 2011) and in general (Wahid et al , 2021), our paper extends this work by showing that correlates of research productivity are not equally relevant across the different types of institutions. Specifically, by building on the JD-R model and considering different levels of teaching demands, we show that correlates of research productivity vary by the type of school, categorized by teaching load, a key job demand.…”
Section: Discussionsupporting
confidence: 69%
“…Thus, the prolific researchers warrant our attention as they have been "drivers" of research activity and impact. Recent studies have systematically analysed factors associated with successful researchers and their academic engagement and publication productivity (Heng, Hamid, and Khan 2020;Perkmann et al 2021;Wahid, Warraich and Tahira 2021) and the public's views of scientists' motivation for their research work (Johnson and Dieckmann 2020), however studies that focus on why some researchers publish prolifically, especially in top journals in their fields and their motivation for success has not been yet explored within the field of Library and Information Science (LIS) research, despite the importance of this topic. For these reasons, it is timely to address key characteristics and their motivation associated with being highly prolific in scholarly publishing.…”
Section: Introductionmentioning
confidence: 99%